Regionalism in Eastern Asia - Skulska, Bogusława (Regionalizm w Azji Wschodniej, 2009)
The development of regionalism in Eastern Asia has been observed since the beginning of the 1990s. The integration processes progressing in this region of the world have currently acquired a specific form absent on other continents. Strong institutionalisation, such as the one in Europe, is not present there, nor has there emerged a leader imposing the direction and shape of the integration processes, similar to North America. Asian regionalism is characterised by the reluctance to form regional political institutions, the dominant role of international production chains in the region, the creation of networks of bilateral FTA and EPA agreements as well as the strive for the development of cooperation between local financial markets following 1997.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 24-33
Keywords: regionalism; economic globalisation; Eastern Asia